PENERAPAN METODE PEER TEACHING DALAM UPAYA MENINGKATKAN HASIL BELAJAR PRAKTIKUM AKUNTANSI PERUSAHAAN JASA, DAGANG DAN MANUFAKTUR PADA SISWA KELAS XI AKL 3 SMKN 1 DUMAI TAHUN 2022 - Misra, Misra (Benefit: Journal of Bussiness, Economics, and Finance, 2023)
This study aims to improve the learning outcomes of Service, Trade and Manufacturing Companies Accounting Practicum with the Peer Teaching learning method. The formulation of the problem that has been compiled by the researchers is: "Is using the Peer Teaching method able to improve learning outcomes for Service, Trade and Manufacturing Company Accounting Practicum for Class XI AKL 3 students at SMK Negeri 1 Dumai, This research is carried out in the form of classroom action research in 2022, in odd semesters. The subjects of this study were 35 students of Class XI AKL 3. Data analysis used descriptive qualitative analysis. Research determines the aspects observed in each indicator of learning outcomes.The results of the research in the chapters that have been discussed can be concluded that using the Peer teaching method can improve student learning outcomes of Class XI AKL 3 SMK Negeri 1 Dumai, the subject of Accounting for Service Companies, Trade and Manufacturing on the subject of Practicum Accounting for Service Companies, Trade and Manufacture. After taking action in the first cycle, students' cognitive learning outcomes increased student learning outcomes. the basic score with an average of 68.71 increased in the first daily test to 82.05 with a completeness level of 97.14%. In Daily Deuteronomy II it increased to 90.18 with a 100% completeness level. Then obtained an increase in learning outcomes from repetition I and repetition II which is very significant.